(untitled) (Global Journal of Management and Business Research, 2017)
Advertising plays a vital role in any country. Quality of the product offered by this sector is crucial for survival and for the economy. This study aims at determining the deceptive advertising provided by different skin care products in Bangladesh. It takes into account the purchasing behavior is difference between male and female students. A sample of 80 undergraduate students was taken from the Jahangirnagar University, Savar-1342, Dhaka, Bangladesh. The results show that deceptive advertising has most impact on consumer buying behavior through deception. There are some laws but not in practice to ensure consumer right and protect them from any deception in Bangladesh. Also there is no specific and strict program code and advertising code like our neighboring country India.